ENVIRONMENTAL MANAGEMENT UNDER THE PERSPECTIVE OF AN AUTOMOTIVE CENTER: A CASE STUDY IN THE CITY OF SANTA MARIA/RS - Lazarotto, Daniel; Ibdaiwi, Thiago Kader Rajeh; Almeida, Damiana Machado de; Costa, Vânia Medianeira Flores; Lopes, Luis Felipe Dias; Santos, Rita de Cássia Trindade dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
For companies linked to the auto industry, the concern for the environment is paramount, especially for generating large quantities and variety of environmentally harmful waste. Andrade et al (2002), one of the strategies for these organizations is to improve their production processes, with the elimination/reduction of losses and waste generation throughout the value chain. The aim of this study is to identify the applicability of an environmental management program in a Automotive Center located in Santa Maria/RS. For this we carried out a survey of bibliographic and descriptive nature of qualitative approach with the strategy case study. Data collection was conducted through semi-structured interviews with the manager of the company and previously structured questionnaire administered to employees. The results obtained show that the company seeks to dispose waste in an environmentally friendly way, still needing enhance these processes. Regarding the implementation of the EMS - is it important to measure the cost of all benefits provided to the company, such as reinforcing a positive image of the company, before compliance with environmental laws, clean and safe work environment, reducing the risk of accidents and waste disposal .